Liver Haemorrhagic Syndrome in Broilers: Its Effect on Serum Parameters, Antioxidant Capacity, Liver Enzymes and Fatty Acid Profile of Liver - Ismail Yavaş; Shahram Golzar Adabi; Necmettin Ceylan (Veterinary Medicine and Science)
ABSTRACT This study sought to evaluate the occurrence of various degrees of liver haemorrhagic syndrome (LHS) in broilers subjected to commercial rearing conditions. The objective was to investigate the influence of lesion scores on various biochemical parameters. The prevalence of liver lesions graded from 0 to 5 was 12%, 31%, 33%, 15%, 6% and 3%, respectively. The crude protein content decreased, whereas the crude fat content increased in Scores 4 and 5 (p < 0.05). The observed increase in thiobarbituric acid reactive substances (TBARSs), carbonyl and sulphydryl levels in Score 5 (82.8%, 43.3% and 74.8%, respectively) suggests that this score may be more susceptible to oxidation compared to livers with no LHS incidence (p < 0.01). A reduction in total protein in Scores 4 and 5, a decline in albumin in Score 5, an elevation in uric acid and gamma‐glutamyl transferase (GGT) in Scores 4 and 5 as well as a rise in cholesterol and alanine transaminase (ALT) in Score 5 were noted (p < 0.05). Furthermore, there was an increase in aspartate transferase (AST) levels in 3, 4 and 5 (p < 0.01). A comparison of the antioxidant data indicated a significant enhancement in the levels of superoxide dismutase (SOD), glutathione peroxidase (GSH PX) and total antioxidants in Scores 1–3, compared to the control group. The lowest levels of SOD, GSH PX and total antioxidants were observed in livers scored 4 and 5 (p < 0.01). Besides, an increase in total saturated fatty acids and a decrease in total monounsaturated fatty acid (MUFA), n‐6, n‐3 and polyunsaturated fatty acid (PUFA) levels were observed in livers scored 4 and 5 when compared to the other groups (p < 0.05). In conclusion, this study has demonstrated that elevated levels of LHS scores are associated with a detrimental impact on the physicochemical and oxidative quality of livers and blood serum.